2024
DOI: 10.1002/cplu.202300726
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of a Polar Nematic Phase: A Chemist's Insight into the Ferroelectric Nematic Phase

Ewan Cruickshank

Abstract: The discovery of a new polar nematic phase; the ferroelectric nematic, has generated a great deal of excitement in the field of liquid crystals. To date there have been around 150 materials exhibiting the ferroelectric nematic phase, in general following three key archetypal structures with these compounds known as RM734, DIO and UUQU‐4N. In this review, the relationship between the molecular structure and the stability of the ferroelectric nematic, NF, phase will be described from a chemist’s perspective. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 76 publications
0
0
0
Order By: Relevance
“…The N F phase of RM734 is perfectly miscible with, and therefore also identical to, the lowest temperature range nematic phase in DIO 3 , 7 . Ferroelectric nematics today constitute an intense field of research 1 41 (so far about 150 N F materials have been reported 23 , 42 , 43 ) but the mechanisms behind spontaneously polarized nematics are still not fully understood. Especially, this holds true for the additional phase, originally called M2, located between the N F phase and the N phase in the archetype N F material DIO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The N F phase of RM734 is perfectly miscible with, and therefore also identical to, the lowest temperature range nematic phase in DIO 3 , 7 . Ferroelectric nematics today constitute an intense field of research 1 41 (so far about 150 N F materials have been reported 23 , 42 , 43 ) but the mechanisms behind spontaneously polarized nematics are still not fully understood. Especially, this holds true for the additional phase, originally called M2, located between the N F phase and the N phase in the archetype N F material DIO 2 .…”
Section: Introductionmentioning
confidence: 99%